EDUKASI PENCEGAHAN STUNTING KEPADA KELOMPOK POSYANDU KAMPUNG BULO KABUPATEN KEPULAUAN SANGIHE - Surudani, Conny Juliana; Makahaghi, Yenny B.; Pangandaheng, Nansy D.; Karimela, Ely John; Pumpente, Obyn I.; Tomasoa, Aprelia M.; Rieuwpassa, Frets (Batara Wisnu : Indonesian Journal of Community Services, 2025)
Stunting prevention by providing knowledge to women, prospective mothers, and mothers is one way to prevent the risk of stunting early on. Education can be given to community-based preventative and promotive care (Posyandu) cadres as the smallest unit of health care for mothers and children. Posyandu cadres of Bulo Village were the purpose of this service activity. The purpose of the service was to provide stunting prevention education to Posyandu cadres of Bulo Village. The activity stages included the team conducting a survey to find out the level of education and age of the Posyandu cadres; then the team conducted education by providing material on the 10 steps to prevent stunting. The results of the service activities showed an increase in knowledge of Posyandu cadres from 53% to 87% after being given material on stunting prevention. It is recommended to educate Posyandu cadres regularly so that awareness about the importance of preventing stunting continues to increase